Trains breaking-up safety control at hump yards - Бантюкова, Світлана Олександрівна (Eastern-European Journal of Enterprise Technologies, 2015)
Mathematical models of trains breaking-up safety control at hump yards and determination of recommended control parameters of car retarders are considered. A general mathematical model of the classification process is absent, evaluation and accounting of numerous impacts on the classification process safety are insufficient, consideration and regulation of individual process components of classification yards cause the need for additional research in this area. Based on the developed models, there is a possibility of rational trains breaking-up safety control by minimizing the risks that may occur at the hump yard. Herewith, the human factor effect on the classification process is largely taken into account. Recommended control parameters of car retarders are determined by the criterion of the minimum number of onsets of each cut on the hump yard slope, the number of overspeeds of entry of each cut to the of retarders of brake positions and the number of overspeeds of impact of each cut with other cuts at classification yard. The models provide efficient safety control of breaking up trains and allow to increase the safety and efficiency of the hump yard process.